Dakwah Bil Hal di Era Modern: Membangun Kepercayaan Umat melalui Pengelolaan ZIS dan Haji yang Profesional - Nur Ilmi; Elli Susanti; M. Nasor (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to describe in depth the professional management system of zakat, infaq, and shadaqah (ZIS) and hajj/umrah, which is the most effective form of da'wah bil hal in the modern era to rebuild the trust of the people gained from sharia values, namely transparency, accountability, and efficiency in managing public funds. Using a descriptive qualitative approach, data was collected through literature study. The results show that modern ZIS institutions not only distribute aid (charity) but also build an ecosystem of economic justice (social justice), which is the essence of substantive Islamic da'wah. The development of Hajj/Umrah management is also a form of da'wah bil hal that is in progress but is not yet fully effective. Therefore, this improvement is not merely an administrative improvement, but the grounding of Islamic values that are rahmatan lil 'alamin through structured, accountable, and impactful social work.